Corruption and environmental policy: An alternative perspective - Athanasios Lapatinas; Anastasia Litina; Eftichios S. Sartzetakis (Fondazione Eni Enrico Mattei (FEEM), 2011)
We construct an overlapping generations model in which agents live through two periods; childhood and adulthood. Each agent makes choices only as an adult, based on her utility that depends on her own consumption and the human capital and environmental quality endowed to her offspring. Entering adulthood, agents choose randomly between two occupations: citizens and politicians. Citizens are the only producers of a single good and choose the proportion of their income to declare to the tax authorities. Politicians decide upon the allocation of the tax revenue between environmental protection and education activities, taking as given the rates of peculation in each activity. In this context, two self-fulfilling stable equilibria can emerge, one associated with high and another with low corruption. Corrupted politicians induce high levels of tax evasion, reducing total public funds and thus environmental protection activities. This result is in accordance with existing empirical evidence and implies that environmental policies may fail in corrupt countries where they are used as means of supporting rent seeking activities instead of protecting the environment. A higher level political authority could intervene and force the low corruption equilibrium by choosing the appropriate tax rate and, through institutional changes, the rates of peculation.
Keywords: H2; H26; H3; Q56; Q58; 330; Corruption; Environmental Policy